Electrostatic Separation of Pyrite From Coal. (1995) - Butcher, D. A.; Rowson, N. A.
Abstract : This paper reviews the various forms of electrostatic separation available to remove sulphur, in the form of pyrite (FeS2 ) from coal. Research has been carried out to desulphurise coal using an electrostatic roll separator which uses the corona charging technique. Data is presented here to conflict with previous reports that indicated that the electrostatic roll separator is unable to separate pyrite from coal. Separation was undertaken under various atmospheric conditions, with various feed pretreatments.